Effect of exercise in the recovery process after the inflammation process caused by coronavirus - Córdova-Martínez, A.; Pérez-Valdecantos, D.; Caballero-García, A.; Sarabia, J. M.; Roche, E. (Journal of Human Sport & Exercise, 2023)
Coronavirus (SARS-CoV-2 - COVID-19) disease causes severe acute respiratory syndrome. During infection, activation of macrophages and pro-inflammatory granulocytes produces cell damage, inducing lung inflammation that leads to the characteristic symptoms of fever, cough, fibrosis, and high increase in pro-inflammatory cytokine levels. In general, during the inflammatory process and infection by coronavirus, cytokines are elevated, particularly IL-1, 6 and 12, TNF-a, and TGF-ß. In addition, patients with complications and lethal prognosis present increased serum levels of IF-I and Gamma compared to healthy individuals or patients with moderate symptoms. On the other hand, it is known that physical activity favours an adaptation of the immune system function. In this context, we suggest that appropriate exercise programs could improve recovery of people who have suffered from COVID-19 disease, improving the quality of life and reinforcing the protection against future infections. The immunomodulatory properties of exercise and physical activity could act as prevention tools for different chronic diseases in healthy individuals and complement therapeutic tools in sick patients. Nevertheless, exercise must be adequate both in time and intensity, taking into account the patient's clinical situation as well as their previous physical activity.